KEPEMIMPINAN KIAI DALAM SITUASI DARURAT SOSIAL : KEPEMIMPINAN KARISMATIK DAN TANTANGAN PERUBAHAN TATA KELOLA PESANTREN - Fadil Muhammad Haqqi; Ali Maskur; Nurkafidz Nizam Fahmi (MPI STAI Sangatta Kutai Timur, 2025)
This study aims to analyze the leadership of kiai (Islamic scholars) in responding to social emergencies and examine the controversy surrounding charismatic leadership amidst demands for change in the governance of modern Islamic boarding schools (pesantren). The focus of the study is on how kiai charisma functions as a legitimizing force for leadership while also presenting challenges in adaptive and participatory decision-making processes during crises. This study uses a qualitative case-study approach, employing data collection techniques such as in-depth interviews, participant observation, and analysis of Islamic boarding school institutional documents. The results show that Kiai's charismatic leadership has proven effective in maintaining social stability and student obedience during emergencies, but at the same time has the potential to hinder governance innovation if not accompanied by systematic managerial mechanisms. This study also found an urgent need for leadership transformation towards a collaborative model that remains rooted in Islamic boarding school values. The contribution of this study lies in strengthening the theoretical perspective of religious leadership in the context of social crises and developing strategic recommendations for adaptive, sustainable, and contextual Islamic boarding school governance to meet changing times.